Realização de um sonho: significado cultural da gravidez para gestantes adolescentes - Santos, Carolina Carbonell dos (2013)
This study is grounded in the concept of culture and Clifford Geertz aimed to understand the meaning that the pregnant adolescent attributed her pregnancy. It was descriptive qualitative approach. Interviews were conducted with 8 teenagers between 13 and 19 years old, attended prenatal in a basic health unit in the interior of Rio Grande do Sul The study took place from March to July 2012. For data collection were used narrative interviews and participant observation as fundamental techniques. As a complementary technique to generate the data, we used the design silhouette of pregnant adolescents, representing how they see themselves in this time of pregnancy. We adopt a thematic analysis, which consists in discovering the core senses. The proposed study was approved by the Center for Continuing Education of Municipal Health Department of Santa Maria and the Ethics Committee of the Universidade Federal de Santa Maria in the number of CAAE 00554512.0.0000.5346. The results show themes - The meaning of motherhood to teenage mothers; - The experience of teenage pregnancy in the family and social; - Expectations of teenage pregnancy in the future. The results showed themes - The meaning of motherhood to teenage mothers; - The experience of teenage pregnancy in the family and social - Expectations of teenage pregnancy in the future. The results obtained in the analysis of data in search of understanding the cultural significance of pregnancy for pregnant teenagers, demonstrated the uniqueness of the process that has culture as a mediator of personal experiences. The findings of this study indicate the importance of understanding the cultural context of the pregnant adolescents to provide care according to their actual needs. We hope that this research will provide its readers a critical analysis of teenage pregnancy, thus overcoming paradigms extant studies in the health field, looking out over this phenomenon from a biological perspective and pathologizing. Thus, it is expected to contribute to both nurses and for other health professionals, improving the quality of health care for adolescents, seeking enhancement of knowledge and practice of these subjects.